Marfan syndrome and exercise: A literature review. Issue 6 (6th August 2020) - Jensen, Tanja Laerke; Tran, Peter; Kjaer, Michael
Abstract: Marfan syndrome (MFS) is an autosomal dominant condition caused by a mutation in the fibrillin‐1–producing gene within the connective tissue, which can affect multiple organ systems negatively, including those that play a vital role (eg, heart and vasculature) in physical activity. The most fatal manifestations of MFS are aortic dilation, dissection, and rupture but to what extent regular physical activity will influence this is sparsely described. The current guidelines for MFS and physical training are based on limited research, and this review aims to summarize human and animal studies on exercise and its influence upon MFS presentation. Most studies found positive effects of regular mild to moderate aerobic exercise upon aorta expansion, as well as upon dilation and hypertrophy of the left ventricle together with a positive training response upon aerobic capacity. However, from the present studies, it is not possible to conclude regarding optimal intensity, frequency, duration, and type of exercise. Overall, the guidelines for exercise in MFS patients have so far due to limited research been relative conservative, despite the fact that at least moderate exercise in combination with tight cardiac monitoring does not demonstrate any detrimental effect upon MFS presentation.